3.4k views
1 vote
to the equation . Where did the student go wrong? Step 1. Factor the polynomial into (x + 6) and (x - 2)Step 2. x - 6 = 0 and x + 2 = 0Step 3. x = 6 and x = -2

User Elian
by
5.8k points

1 Answer

2 votes

Answer and explanation:

The wrong step is changing the sign in step 2

Such that; in step 1 the student had; (x + 6) and (x - 2)

In step 2, the student should have;

x + 6 = 0 and x - 2 = 0 instead of x - 6 = 0 and x + 2 = 0

Step 3, will thus be;

x = -6 and x = 2

User Davvs
by
5.2k points